Enhancing Energy Generation Through Floating PV Integration with Existing Hydropower Station - Hnin Yu Wai; Wunna Swe; Swe Zin Oo (The Indonesian Journal of Computer Science, 2025)
In this paper, the design and performance of an integrated floating photovoltaic (PV) system at the Kun Chaung Hydropower Station in Myanmar are analyzed. Hybridizing grid-connected hydropower with floating PV enhances renewable energy output. A site assessment evaluates the reservoir’s suitability, considering solar irradiance, water levels, and environmental impacts. The proposed design includes PV module specifications, floating structures, and system integration. Energy output is analyzed under various conditions. Results show that the minimum hydropower generation in April, 24343 MWh, increases to 33865 MWh with floating PV, while maximum generation in November rises from 40878.2 MWh to 47768.6. Integration improves system capacity, ranging from 56.74 MW in May to 117.68 MW in October. These findings confirm the potential of floating PV to enhance energy generation. The study concludes with recommendations for implementation and highlights future research opportunities to optimize performance and assess economic feasibility.